THE INFLUENCE OF THE RECRUITMENT AND SELECTION PROCESS ON EMPLOYEE PERFORMANCE AT THE DONGGALA DISTRICT BALITBANGDA OFFICE - Tri Januarti; Idris; Bakri Hasanuddin; Pricylia Chintya Dewi Buntuang (RADJA PUBLIKA, 2025)
This study aims to examine the impact of the recruitment and selection process on employee performance at the Balitbangda Office of Donggala Regency. This study uses an associative quantitative method involving 40 employees selected through a saturated sampling technique. Data collection was carried out through questionnaires and analysis was carried out using multiple linear regression using SPSS version 23. The findings show that recruitment has a positive and significant impact on employee performance, with a significance value of 0.004. Meanwhile, selection also shows a positive and significant impact with a significance value of 0.005. Simultaneously, recruitment and selection show a significant influence on employee performance with a significance value of 0.000 and an R Square of 0.823, which means that both variables can explain 82.3% of the variation in performance. The results of this study are in line with the existing situation at Balitbangda, where there are problems such as delays in research reports and competency mismatches among employees. Therefore, it is important to improve competency-focused recruitment and conduct objective and transparent selection so that employee productivity and professionalism can be increased. The findings of this study are expected to provide input for Balitbangda in improving human resource management policies.